The effect of substrate surface preparation on the wear and failure modes of titanium nitride coated high speed steel circular saw blades - Bradbury, S R; Lewis, D B; Sarwar, M (Wear, 1996)
The effect of substrate surface preparation on the performance and tool life of titanium nitride coated high speed steel circular saw blades has been shown to be significant. The influence this has on the wear and failure characteristics of the blades is not considered. Previous work by the authors shows titanium nitride coated high speed steel circular saw blades benefit from substrate surface preparation prior to treatment. Cutting test results show that blades which had undergone a microblasting process exhibited an increase in tool life. Using testing methods developed to simulate the cutting action of full circular saw blades by using representative saw segments, the effects of substrate surface preparation are further investigated by identifying and comparing the wear mechanisms that develop on circular saw teeth subject to various preparation/coating conditions. Assessment of the wear and failure mechanisms associated with each combination of substrate preparation/coating have been used to appraise the relative merits of the treatment, blade design and manufacturing process. The work will assist in the development of a systems approach that combines both cutting tool and surface engineering technologies with a view to developing an improved product.